1995
DOI: 10.1046/j.1537-2995.1995.35895357897.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet concentrates promote procoagulant activity: evidence from experimental studies using a perfusion technique

Abstract: While the preparation and storage of platelets have a detrimental effect on platelet adhesiveness, such procedures can positively influence the platelet procoagulant activity necessary to platelet hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…The results on Day 5 in PCs treated with 6.2 J per mL are in favorable contrast with previous experience from our group. We have previously communicated that adhesive and cohesive functions of PLTs tend to decrease with storage time 35 . Although results from perfusion experiments with PCs exposed to higher levels of energy showed a progressive reduction in adhesive and cohesive functions of PLTs on the 5th day, those from PCs treated with 6.2 J per mL did not show such a decay.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results on Day 5 in PCs treated with 6.2 J per mL are in favorable contrast with previous experience from our group. We have previously communicated that adhesive and cohesive functions of PLTs tend to decrease with storage time 35 . Although results from perfusion experiments with PCs exposed to higher levels of energy showed a progressive reduction in adhesive and cohesive functions of PLTs on the 5th day, those from PCs treated with 6.2 J per mL did not show such a decay.…”
Section: Discussionmentioning
confidence: 93%
“…These would indicate the existence of a threshold in illumination energies from 6.2 to 12.3 J per mL that may have a critical impact on PLT quiescence. Nevertheless, studies from our group have demonstrated that loss of adhesive and aggregating properties in PLTs subjected to prolonged storage might be partially compensated by the development of procoagulant activity 35,36 . Interestingly, this procoagulant activity is the direct result of the exposure of negatively charged phospholipids and revealed by an increased annexin V binding to the PLTs or their derived microparticles.…”
Section: Discussionmentioning
confidence: 96%
“…Results from controlled in vitro experiments [25] allow us to discard that the volume of plasma infused with the platelets could be responsible for the increase ob served in fibrin deposition. Increased levels of TAT com plexes were also found in posttransfusion plasma samples, which further reinforces the impression that the transfusion of HLA-incompatible platelets were at least able to activate coagulation in this group of refractory patients.…”
Section: Discussionmentioning
confidence: 99%
“…To reproduce conditions found in patients with severe thrombocytopenia (<10,000 μL) caused by marrow failure, PLTs and WBCs were filtered from normal blood samples with WBC reduction filters (RC100 PALL Corp., Glen Cove, NY) (n ≥ 6). Details of this procedure have been described elsewhere 20,27 . Before the initiation of perfusion, blood samples were incubated for 1 minute with either diluent in the absence of rFVIIa (baseline) or aliquots of rFVIIa calculated to reach concentrations of 2.5, 5, and 10 μg per mL at the plasma interface (n ≥ 6).…”
Section: Methodsmentioning
confidence: 99%
“…Fibrin deposition and PLT interactions with the subendothelium were evaluated with light microscopy and a specially devised software that automatically classifies and quantifies PLT and fibrin coverage 20,28 following the criteria described by Turitto and Baumgartner 29 . For simplicity, PLT interactions were globally expressed as the total percentage of the vessel surface covered.…”
Section: Methodsmentioning
confidence: 99%